Challenges facing women entrepreneurs in accessing loans from microfinance institutions: The case of Dar es Salaam - Langa, Neema (Mzumbe University, 2024)
A dissertation submitted to Mzumbe University as a partial fulfillment of the requirements for the award of Master Degree of Business Administration Corporate Management (MBA.CM) of Mzumbe University.